Des marginaux et des délestés : figures victimaires de la pandémie dans le débat québécois autour des personnes non-vaccinées contre la Covid-19 - Gattiglia, Nora (Ponti/Ponts, 2024)
On 11th, January 2022, the Legault government in Quebec anticipates a taxation on whose who have not been vaccinated against Sars-Cov-2. The news triggers a lively debate on the general appropriateness of sanctions against those who do not follow the national health recommendations. This article analyses 378 comments by the readers of the online newspaper Le Devoir. The relative controversy has to do with the foundations of democratic coexistence: questions are raised as to how to maintain the social contract at a time when the exercise of individual freedoms runs counter to the well-being of the community. But above all, it is the ties that hold the Quebec community together that are called into question. The debate on government measures expresses underlying tensions, including the relationship to minorities – in this case, the unvaccinated. Should their freedoms be limited to protect the majority? Or does any minority have a right to self-determination? This article addresses the recurrence of a specific figure, that of the “victim ” within the debate, embodied by both the unvaccinated, portrayed as a marginalized minority, and the cancer patient being prevented from receiving treatment due to the overburdening of the national health system. Both figures are at the core of two opposing discourses of victimisation, constructing the figure of the victim as a peculiar variation of the notion of minority that signals fundamental social changes. By studying the debate around unvaccinated people and the relationship between this minority category and a society that does not know how to manage a threatening otherness, I propose to investigate the peculiar dynamics of victimisation in the Quebec debate, and the impossibility to reach a decision when the argumentation is built around this specific strategy.